2019
DOI: 10.1371/journal.pone.0218426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health service interventions on acute hospital use in community-dwelling persons with dementia: A systematic literature review and meta-analysis

Abstract: Background Persons with dementia have twice the acute hospital use as older persons without dementia. In addition to straining overburdened healthcare systems, acute hospital use impacts patient and caregiver quality of life and is associated with increased risk of adverse outcomes including death. Reducing avoidable acute hospital use in persons with dementia is thus a global healthcare priority. However, evidence regarding the impact of health service interventions as defined by the Effective Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…Shorter interventions led to better mental functioning scores (Amo‐Setien et al., 2019); longer interventions improved HbA1c levels but not blood pressure (Berntsen et al., 2019). Longer case management interventions in dementia were associated with reduced institutionalisation (Pimouguet et al., 2010), but not for other care models compared to usual care (Godard‐Sebillotte et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shorter interventions led to better mental functioning scores (Amo‐Setien et al., 2019); longer interventions improved HbA1c levels but not blood pressure (Berntsen et al., 2019). Longer case management interventions in dementia were associated with reduced institutionalisation (Pimouguet et al., 2010), but not for other care models compared to usual care (Godard‐Sebillotte et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Having a clear focus on self‐management contributed to positive clinical outcomes in LTCs and multimorbidity (Kastner et al., 2018; Reynolds et al., 2018), social support in LTCs (compared to usual care) (Reilly et al., 2015), and reducing admissions in older people at risk of hospitalisation (Tricco et al., 2014); but did not influence the effectiveness of case management over usual care upon acute hospital use for people with dementia (Godard‐Sebillotte, Le Berre, Schuster, Trottier, & Vedel, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers of two recent systematic reviews, however, have found little evidence to support health services interventions successfully reducing acute hospitalizations or emergency department visits. One group of researchers who conducted a recent systematic review and meta‐analysis of 17 randomized controlled trials from seven countries aimed at reducing avoidable acute hospital care by community‐dwelling individuals with dementia found that none of the interventions reduced acute hospital use, such as emergency department visits, hospital admissions, or hospital days 653 . In another systematic review and meta‐analysis that included some of the same studies, researchers also found no evidence that non‐pharmacological interventions reduced hospital admission for community‐dwelling individuals with dementia 654 .…”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…Another group of researchers, however, found that a dementia care program that used nurse practitioners and physicians to co‐manage patients was cost neutral after taking into account the costs of the program and cost savings due to fewer long‐term care nursing home admissions 585 . However, in a recent systematic review and meta‐analysis of 17 randomized controlled trials from seven different countries aimed at reducing avoidable acute hospital care by persons with dementia, none of the interventions reduced acute hospital use, such as emergency department visits, hospital admissions, or hospital days 586 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%